Language Assessment Course: Impact on Pre-service EFL Teachers’ Language Assessment Literacy - Entika Fani Prastikawati; Januarius Mujiyanto; Mursid Saleh; Sri Wuli Fitriati (Universitas Negeri Semarang, 2021)
Being an assessment literate has never been as critical and crucial as it is today. The existence of a language assessment course has been obligatory for the English education department to support the development of pre-service EFL teachers’ language assessment literacy. This study is intended to examine the impact of a language assessment course on pre-service EFL teachers’ language assessment literacy. A total of 134 pre-service EFL teachers completed Assessment Literacy Inventory (ALI) as pre-test and post-test of assessment literacy measures. To measure the significant difference in language assessment literacy, a series of dependent sample t-test was carried out. The result revealed a significant improvement in language assessment literacy after pre-service EFL teachers completed their language assessment course. Certain aspects of Standard in assessment literacy were in non-significant development.